Diversity of bacterial community in the rhizosphere and bulk soil of Artemisia annua grown in highlands of Uganda. - Namuli Aidah; Ogwang Patrick Engeu; Tumuhairwe John Baptist; Vincent B Muwanika; Mayega Johnson; Bazira Joel (PLoS ONE, 2023)
High land areas in Uganda are suitable for the farming of Artemisia annua. However, harvested A. annua from these areas contain varying concentrations of antimalarial components. This may be attributed to variation in soil properties which affect vegetative growth characters, yield and active compounds of A. annua. Thus, bacterial composition and physiochemical properties of soil from Kabale and Kabarole high land areas where A. annua is grown were studied. The study objective was to determine the diversity of bacterial community in the rhizosphere and bulk soil of A. annua grown in highlands of Uganda. Composition of bacterial community was analyzed by amplicon sequencing of 16S rRNA genes on an Illumina Miseq platform. A total of 1,420,688 read counts was obtained and clustered into 163,493 Operational Taxonomic Units ((OTU). Kabarole highland had more OTUs (87,229) than Kabale (76,264). The phylum Proteobacteria (34.2%) was the most prevalent followed by Acidobacteria (17.3%) and Actinobacteria (15.5%). The bacteria community in the two highlands significantly differed (p <0.05) among all phyla except Proteobacteria. The main genera in bulk soil were povalibacter, brevitalea, nocardioides, stenotrophobacter, gaiella and solirubrobacter. Sphingomonas, ramlibacter paludibaculum and pseudarthrobacter were the main genera in A. annua rhizospheric soil.